Myth about altruistic organic consumption : values influence in perceiving organic meat consumer - Kortelainen, Sirpa (2015)
The aim of this study was twofold: Firstly, to find out whether organic meat consumers are perceived pro-social as defined by Griskevicius et al (2010) with attributes: Caring, Altruistic and Nice. The second theme was to find out what values of the perceiver influence that judgement; a glimpse to who finds the organic bacon consumer as pro-social. Quantitative methods were used in this study and an internet survey was conducted within students of University of Helsinki and Aalto University as well as a pre-requited Food West panellists. As anticipated, the results show that the organic bacon consumer is indeed perceived significantly more pro-social than the user of conventional bacon. The results indicate that conservational values: conformity, security and tradition best explain the pro-social perception on the organic bacon consumer although also hedonism was found influential in forming the perception. Further the analysis reveals that the conservational values importance to the person influence the perception on organic bacon consumer especially within women. Thus, based on the results it could be hypothesised that the person who perceives organic bacon consumer as pro-social is a woman who cherishes conservational values and that the strength of the values determines her perception. This study contributes new insight to the theory about the influence of values in forming a perception on organic food (meat) consumers. The implications drawn from the study can also be used to benefit organisations and producers in the organic food sector. Empowerment of consumers could be one way to guide consumers for more pro-environmental consumption behaviour as it could trigger both, the conservational values as well as hedonism from the selfenhancement value domain. The rapid growth of alternative agro-food networks such as local food and urban agriculture suggests that consumers are looking for ways to participate in the food system and through participation empower themselves; Resulting in more pro-environmental consumption behaviour.